Synergies and trade-offs between agricultural export promotion and food security: Evidence from African economies - Aragie, Emerta A.; Balié, Jean; Morales, C.; Pauw, Karl (Elsevier, 2023)
Several countries across the developing world have designed and implemented agricultural export incentives. However, little is known about the effects of these policies on various aspects of domestic food security. This study utilizes economywide models linked top-down with microsimulation modules to analyze the impacts of increased agricultural export promotion on the four dimensions of food security – availability, access, utilization, and stability – in three structurally food-insecure economies of Ethiopia, Kenya, and Uganda. We find that agro-export promotion adversely affects all four aspects of food security in urban areas and at the national level due to significant increases in food prices domestically. However, it generally benefits households in rural areas. The food security effects are stronger in Ethiopia and Kenya. We also find that risks associated with the volatility in international markets and declines in domestic productivity can lead to further deterioration in access to food when countries implement outward-oriented agricultural policies